Normative body dissatisfaction and eating psychopathology in teenage girls: the impact of inflexible eating rules - Duarte, Cristiana (2015)
Adolescence has been considered a critical time for the development of body image-related difficulties and disordered eating behaviours, especially in females. Although adherence to eating rules has been linked to disordered eating, literature has not yet explored how the inflexible subscription to those rules impacts on eating psychopathology. Therefore, the aim of the current study was to explore whether inflexible eating impacts on the relationships between weight and body image-related variables, and disordered eating.